Gear up for 2023 towards GRU 2025 - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
The workshop has successfully projected strategic initiatives from 7 divisions which were academic, recruitment and admission, research, course work and mixed mode, academic development, recourses and student, strategic planning and academic quality, as well as administration. Each division has been assigned the task to plan and strategize the activities throughout 2023. All projected initiatives will be documented and distributed among IPSis staff to ensure this strategic plan is successful and effective and aligned with UiTM GRU 2025. The workshop ended on 13th January 2023.